HUBUNGAN KUADRATIK JUMLAH DAN LETAK SEED DENGAN DISTRIBUSI DOSIS I-125 BRACHYSEED PADA MODEL KANKER PROSTAT MENGGUNAKAN DOSE VOLUME HISTOGRAM - Junios, Junios (IAIN Batusangkar, 2012)
The aim of this study is to assess the variation effect of the amount and the location of seed I-125 in dose absorbing behaviors of the target (prostate) and other organs at risk (bladder and rectum). The phantom model is 8x8x8 cm3 cube-shaped with 0.2x0.2x0.2 cm3 voxel size. I-125 seeds are implanted into the prostate with variation of spacing and number. DOSXYZnrc is implemented to calculate doses. To analyze dose distribution of each organ, the Dose Volume Histogram (DVH) program is developed using MATLAB. From this investigation, the effect of location of seeds influences the dose volume histogram for all organs. For example, the volume of prostate that receives 20% or more of the maximum dose (VB20) decrease around 40%, if the spacing among the seeds increases from 0.5 cm to 1 cm. But the spacing of seeds has insignificance effect on VB100 for each organ. This fenomena also appears if the number of seeds is changed. The spacing - and the number of seed have important role in the dose distribution not only on the target but also on the organs at risk. Therefore, the optimization for both parameters is needed.Key words: Brachytherapy, Prostate, DOSXYZnrc, DVH